Beneficial Effects of Two Hydrogen Sulfide (H2S)-Releasing Derivatives of Dexamethasone with Antioxidant Activity on Atopic Dermatitis in Mice - Coavoy-Sánchez, Silvia Abigail; Cerqueira, Anderson Romério Azevedo; Teixeira, Simone Aparecida; Santagada, Vincenzo; Andreozzi, Giorgia; Corvino, Angela; Scognamiglio, Antonia; Sparaco, Rosa; Caliendo, Giuseppe; Severino, Beatrice; Costa, Soraia Katia Pereira; Spolidorio, Luis Carlos [UNESP]; et al. (MDPI, 2023)
Hydrogen sulfide (H2S) is particularly produced in the skin, where it participates in the regulation of inflammation, pruritus, cytoprotection, scarring, and angiogenesis. In this study, we compared the effects of dexamethasone (Dex) with two H2S-releasing Dex derivatives in a murine model of atopic dermatitis (AD) induced by topical application of 2,4-dinitrochlorobenzene (DNCB). After sensitization with DNCB, the animals were topically treated for five consecutive days with either the H2S-releasing compounds 4-hydroxy-thiobenzamide (TBZ) and 5-(p-hydroxyphenyl)-1,2-dithione-3-thione (ADT-OH), Dex, or the derivatives Dex-TBZ or Dex-ADT. Topical treatment with equimolar doses of either Dex, Dex-TBZ, or Dex-ADT resulted in similar reductions in dermatitis score, scratching behavior, edema, eosinophilia, splenomegaly, and histological changes. In contrast with Dex, the H2S-releasing derivatives prevented IL-4 elevation and oxidative modification of skin proteins. On an equimolar dose basis, Dex-TBZ, but not Dex-ADT, promoted the elevation of endogenous H2S production and GPx activity. Neither Dex-TBZ nor Dex-ADT decreased GR activity or caused hyperglycemia, as observed with Dex treatment. We conclude that the presence of H2S-releasing moieties in the Dex structure does not interfere with the anti-inflammatory effects of this corticosteroid and adds beneficial therapeutical actions to the parent compound.
Keywords: atopic dermatitis; dexamethasone; hydrogen sulfide; oxidative stress